1991
DOI: 10.1093/oxfordjournals.humrep.a137267
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of superoxide dismutase in the human ovary

Abstract: To elucidate the physiological function of superoxide dismutase (SOD) in the ovary, we examined the immunohistochemical distribution of CuZn-SOD in the human ovary. We also measured the CuZn-SOD concentration in human follicular fluid by enzyme-linked immunosorbent assay (ELISA). The germinal epithelium and tunica albuginea showed no or weak immunoreactivity. No or weak staining activity was also observed in the non-antral follicle. Once the follicle began to form the antral cavity, theca interna cells began t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 10 publications
2
27
0
1
Order By: Relevance
“…By contrast, it has been also demonstrated that ROS, including superoxide and hydrogen peroxide, play critical roles in the regulation of ovarian functions, such as oocyte maturation, folliculogenesis, ovarian steroidogenesis, and luteolysis. Thus, there is a delicate balance between ROS and antioxidant enzymes in the ovarian tissue (Shiotani et al 1991;Behrman et al 2001;Sugino et al 2004;Agarwal et al 2005;Agarwal et al 2006;Tatone et al 2008). The imbalance of ROS and antioxidants has been suggested as a mechanism of ovarian aging, as shown by decreased levels of glutathione and glutathione S-transferase in ovulated oocytes from aged mouse or downregulation of superoxide dismutase (Cu/ZnSOD and MnSOD) and catalase genes in human granulosa cells (Tarin et al 2004;Tatone et al 2006;Tatone et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, it has been also demonstrated that ROS, including superoxide and hydrogen peroxide, play critical roles in the regulation of ovarian functions, such as oocyte maturation, folliculogenesis, ovarian steroidogenesis, and luteolysis. Thus, there is a delicate balance between ROS and antioxidant enzymes in the ovarian tissue (Shiotani et al 1991;Behrman et al 2001;Sugino et al 2004;Agarwal et al 2005;Agarwal et al 2006;Tatone et al 2008). The imbalance of ROS and antioxidants has been suggested as a mechanism of ovarian aging, as shown by decreased levels of glutathione and glutathione S-transferase in ovulated oocytes from aged mouse or downregulation of superoxide dismutase (Cu/ZnSOD and MnSOD) and catalase genes in human granulosa cells (Tarin et al 2004;Tatone et al 2006;Tatone et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that erythrocyte GPx activity is higher in women than in men (1), and that the activities of SOD and GPx in liver (2) and SOD and CAT activities in macrophages (3) are significantly higher in female rats. The luteal content of SOD changes during the S. Peji et al ovulatory cycle in humans (4), whereas GPx activity in erythrocytes is positively correlated with plasma estradiol levels during the menstrual cycle (5). It has been reported that estradiol influences the expression of SOD in the corpus luteum (6) and significantly alters the activity of CAT (3) and the production of O 2 · -and H 2 O 2 (7) in rat macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…These biomarkers play roles in development of follicles and regulate processes involved in oocyte maturation, steroidogenesis and folliculogenesis (Suzuki et al, 1999). Studies by Shiotani et al (1991) on immunohistochemistry of antral follicles revealed the presence of antibody to Ad4-binding protein, which is a steroidogenic transcription factor that causes transcription of enzymes involved in steroidogenesis. This suggests a close association between steroidogenesis and oxidative stress.…”
Section: Issn: 2320-5407mentioning
confidence: 99%